SIMULASI DESAIN ANTENA MIKROSTRIP U-SHAPE UNTUK KOMUNIKASI 5G (Jurnal Matematika dan Sains (JMS), 2021)
5G technology is expected to start spreading in 2020. Underlies the need for study and research on this technology. This study aims to design an antenna that can be used for Fifth Generation (5G) mobile communication transmission. Designing an appropriate antenna design to provide antenna characteristics by the expected working frequency needs to be done so that antenna performance can be maximized. The manufacture of the antenna is carried out with the stages of the process starting from the study of the material, making the antenna design, then this design is analyzed using the CST Suite 2017 software. The analytical methods used include FDTD, FEM, and, MoM. The simulation with the software aims to get the working frequency in the 5G range, radiation patterns, polarization, gain and, return loss. The results of the simulation are then performed the VSWR characterization, return loss, reflection coefficient, radiation pattern and, gain. Furthermore, comparisons and conclusions can be made. Antennas that have been designed, fabricated and, carried out characterization have concluded that the antenna is capable of working at a frequency of 28 GHz. Characterizatio of the antenna are VSWR 1.295, Return Loss -19.01 dB, Directional radiation pattern and, Gain of 13.2 dBi.